Advanced accounting : a procedural approach vol. 1 - Guerrero, Pedro P.; Peralta, Jose F. (Manila, Philippines : GIC Enterprises & Co, 2013)
This 2013 edition of Advanced Accounting - Volume 2 is designed for financial accounting courses above the intermediate level. The 2013 edition has been updated to reflect recent business development and current changes in accounting standards, especially the coverage of business combination (IFRS 3), and the preparation of consolidated financial statements (IFRS 10). The chapter content is revised for better understanding and efficient coverage. This edition continues to provide a strong presentation of advanced accounting topics, clear discussion, and integrated coverage based on continuous case examples. The text is highly illustrated with complete presentation of worksheets, schedules and financial statements so that students can see the development of each topic.
Home Office and Branch Accounting - General Procedures 1 -- Home Office and Branch Accounting - Special Problems 47 -- Business Combinations (IFRS 3) 89 -- Consolidated Statement of Financial Position - Data of Acquisition 135 -- Intercompany Profit Transaction - Inventories 255 -- Intercompany Gain Transactions - Fixed Assets 303 -- Accounting for Foreign Currency Transactions 347 -- Translation of Foreign Financial Statements 401 -- Government Accounting System for National Government Agencies 433 -- Nonprofit Organizations 495
Keywords: ADVANCE ACCOUNTING--PROCEDURAL APPROACH; ADVANCE ACCOUNTING--PRINCIPLES AND PROCEDURAL APPLICATIONS